2023
DOI: 10.1002/ehf2.14275
|View full text |Cite
|
Sign up to set email alerts
|

Titration of medications and outcomes in multi‐ethnic heart failure cohorts (with reduced ejection fraction) from Singapore and New Zealand

Abstract: Aims We investigated titration patterns of angiotensin‐converting enzyme inhibitors (ACEis)/angiotensin receptor blockers (ARBs) and beta‐blockers, quality of life (QoL) over 6 months, and associated 1 year outcome [all‐cause mortality/heart failure (HF) hospitalization] in a real‐world population with HF with reduced ejection fraction (HFrEF). Methods and results Participants with HFrEF (left ventricular ejection fraction <40%) from a prospective multi‐centre study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A multivariable Cox proportional hazards model was computed to assess the factors associated with reaching the vericiguat maximal daily dose at any given time over the 90 days of follow-up. The model included the time to reach the maximal daily dose during the 90 days of follow-up as the outcome and was adjusted for known predictors of HF medication uptitration [ 26 , 27 ], such as age, sex, comorbidities, and the use of HF medications and non-pharmacological therapies. The model computed hazard ratios (HRs) with 95% confidence intervals (CIs) for each variable included.…”
Section: Methodsmentioning
confidence: 99%
“…A multivariable Cox proportional hazards model was computed to assess the factors associated with reaching the vericiguat maximal daily dose at any given time over the 90 days of follow-up. The model included the time to reach the maximal daily dose during the 90 days of follow-up as the outcome and was adjusted for known predictors of HF medication uptitration [ 26 , 27 ], such as age, sex, comorbidities, and the use of HF medications and non-pharmacological therapies. The model computed hazard ratios (HRs) with 95% confidence intervals (CIs) for each variable included.…”
Section: Methodsmentioning
confidence: 99%
“…12,17,18 Prescription rates of evidence-based therapies in clinical practice: status quo Great variability exists in the prescription rates of each class of agent comprising GDMT for ambulatory patients with HFrEF (Table 1). [10][11][12][13][18][19][20][21][22][23][24][25][26] In 2008, the Registry to Improve the Use of Evidence-Based Heart Failure Therapies in the Outpatient Setting (IMPROVE HF) evaluated 167 outpatient cardiology clinics and showed high prescription rates of beta-blockers (86%) and RAS inhibitors (ACEI or ARB; 80%) in eligible patients but much lower use of MRAs (36%); this was believed to be due to a perceived risk of increased mortality or hospitalization associated with hyperkalaemia as shown after the publication of the RALES and the subsequently wide use of MRAs. 19,27 Moreover, an analysis from the Swedish Heart Failure Registry showed that use of beta-blockers improved from 85% to 93% (p=0.008) between 2003 and 2012, whereas use of RAS inhibitors remained unchanged (88% versus 86%; p=0.091) and the use of MRAs decreased (53% versus 42%; p<0.001) after adjusting for 38 clinically significant baseline variables.…”
Section: Review Use and Optimization Of Pharmacotherapies For The Tre...mentioning
confidence: 99%
“…Previous studies have shown that a significant proportion of patients remain on suboptimal doses of GDMT despite no obvious intolerance or contraindication (Table 1). [10][11][12][13]18,21,22,[24][25][26]46 An analysis from CHAMP-HF showed that very little up-titration occurs in clinical practice, with less than 1% of eligible patients being treated with the triple combination at target doses of a beta-blocker, RAS inhibitor and MRA combination over 12 months. Noteworthy, there were minimal or no changes in dosage at each 3-month visit during follow-up, with most patients The QUALIFY study group proposed an adherence score that was calculated for each patient: 0 points were attributed if medication was not prescribed in the absence of contraindications, 0.5 points if <50% of target doses were prescribed or 1 point for the prescription of ≥50% of target dose of GDMT.…”
Section: Optimization Of Pharmacotherapies For the Management Of Hfre...mentioning
confidence: 99%
See 2 more Smart Citations